Dampak Implementasi Peraturan Perlindungan Data Pribadi terhadap Keamanan Informasi - Panggalo, Ludia (UNIVERSITAS SERAMBI MEKKAH, 2024)
Implementation of personal data protection regulations has become a crucial issue in the increasingly developing digital era, where personal data has become a very valuable commodity. This article examines the impact of implementing personal data protection regulations on information security through a literature review method. By collecting and analyzing various academic sources, this article explores how regulations such as the GDPR (General Data Protection Regulation) in the European Union and similar regulations in various countries influence information security policies in the private and public sectors. The study identified significant changes in data security practices, challenges faced by organizations in implementing regulations, as well as benefits gained in increasing user trust and mitigating risks. The findings of this review show that personal data protection regulations not only influence the way organizations manage data, but also drive improvements in overall information security practices. It is hoped that this article will provide valuable insights for policy makers and practitioners in designing effective information security strategies amidst a dynamic regulatory landscape.